2020
DOI: 10.12659/msm.928538
|View full text |Cite
|
Sign up to set email alerts
|

Lightwand-Guided Insertion of Flexible Reinforced Laryngeal Mask Airway: Comparison with Standard Digital Manipulation Insertion

Abstract: Background The flexibility of the long flexometallic tube makes insertion of the flexible reinforced laryngeal mask airway (f-LMA) difficult. We compared the usefulness of rigid lightwand-guided f-LMA insertion with standard digital manipulation. Material/Methods Fifty-four patients (aged 19–70 years) were randomly divided into a control group (digital manipulation technique) or the lightwand group (lightwand-guided insertion technique). The insertion profiles, orophary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…In the current study, the OLP was comparable in the two groups with no significant difference ( p =0.674). The result is consistent with that of Kim et al ( 13 ). Our findings showed an ideal RLMA placement (Fiberoptic score of 3&4) in 88.7% of the tongue depressor group vs. 67% in the standard group.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the current study, the OLP was comparable in the two groups with no significant difference ( p =0.674). The result is consistent with that of Kim et al ( 13 ). Our findings showed an ideal RLMA placement (Fiberoptic score of 3&4) in 88.7% of the tongue depressor group vs. 67% in the standard group.…”
Section: Discussionsupporting
confidence: 94%
“…Other options described by some authors are the use of a spatula, Bosworth introducers and Flexiguide introducer to facilitate insertion ( 11 ). Kulkarni et al designed an acrylic sheath ( 12 ) while Kim et al ( 13 ) used light wand-guided insertion of the device. All the methods are useful for placement but they are either time-consuming or require preparation and adjustmen( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 5 ] The advancement in anaesthesia practice is towards securing airway devices under vision rather than inserting them blindly, for which several techniques and devices such as laryngoscopes, lightwand, C-MAC videolaryngoscope and other videolaryngoscopeshave been used. [ 6 9 11 12 13 14 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Several studies have reported the effectiveness of under-vision-guided insertion techniques of SGA devices in terms of attaining higher OPLPs. [ 6 9 11 12 ] Kim et al . [ 9 ] in their study, reported higher OPLPs when LMA (LarySeal™ ) was inserted under laryngoscope guidance (21 ± 8.6 cm of H 2 O) when compared to blind insertion technique (18.1 ± 6.1 cm of H 2 O).…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques have been investigated to increase the success rate of SGA device insertion in the first attempt, including the 90° rotation technique, 180° rotation technique, head elevation, or rotation and guidance technique [7][8][9][10][11][12]. Among these approaches, the 90° rotation technique was first introduced by Hwang et al in 2009 [7].…”
Section: Introductionmentioning
confidence: 99%